The sensory in the oral history of Diocina Lopes dos Reis: an invitation to environmental historians - Schwall, Elizabeth (Outros Tempos: Pesquisa em Foco - História, 2025)
This article encourages scholars to work at the intersection of oral history, environmental history, and sensory history to better understand how complex, three-dimensional individuals interacted with and experienced landscapes. To make this argument, the essay examines existing academic literature and then illustrates how focusing on sensory details in an oral history interview can provide fresh insights into environmental histories. The interview at the center of this essay was recorded in 2004 by the Museu da Pessoa, and the narrator is Diocina Lopes dos Reis, a quebradeira de coco babaçu - a woman who extracts babassu coconuts - from Lago do Junco, Maranhão. Lopes dos Reis and other fellow quebradeiras lived through bloody battles over land in the 1970s and 1980s and have successfully commercialized their soap and other coconut byproducts in subsequent decades. Her story is filled with sensory information that foregrounds the gender and class dynamics of environmental history.